Path Loss Measurement and Modeling for Lagos State G.S.M Environments - O, Shoewu; N.O, Salau; A.O, Ogunlewe; L.I, Oborkhale (Review of Computer Engineering Research, 2017)
This paper presents path loss measurement and modeling for Lagos state dense-urban (DU), urban (UR), sub-urban (SU) and non-urban (NU) G.S.M environments. It was carried out with data collection through drive testing using TEMS software in the chosen environments Lagos-Island(DU), Surulere (UR), Lekki-Oniru (SU), Agbede-Ikorodu (NU), over a distance of 0.5-10Km from Base station (BS) to Mobile station (MS) with measurement taken at 0.5Km intervals for a period of 52 weeks. Relative parameters like Rxlev, RSSI, Path loss were measured in all areas of investigation under 2G and 3G frequencies of operation and twelve (12) different sites location were covered and analysed. COST 231-Hata model was used as reference model for path loss calculation of field data, this was further adjusted to develop optimized models (tagged OMODEEN models) for path loss prediction in all environments of study, which shows results within 6dB acceptable range, hence recommended for modeling in these environs and other similar G.S.M environments.